Improving Asthma Management through Iot-Based Telemedicine Spirometry in The Post-COVID-19 Era in Sidoarjo Tofu Making Community, Indonesia - Luthfiyah, Sari; Gumiwang Ariswati, Her; Lusiana; Gede Hari Wisana, I Dewa; Indriatie (Frontiers in Community Service and Empowerment, 2024)
Asthma is a chronic inflammatory disease of the airways that causes recurrent episodes of wheezing, shortness of breath, chest tightness and coughing. The partners in this study face the problem that tofu factories in their area use plastic waste as fuel, which can aggravate respiratory conditions. In addition, the partners need more knowledge about the clear signs of asthma attacks, asthma symptom control and risk factors for asthma patients. The solution provided through the Community Service Programme with the PKM (Student Creativity Programme) scheme is to measure lung volumes using an IoT-based telemedicine device, specifically a spirometry tool that can be used with an Android mobile phone. In addition, partners will receive support to improve their knowledge, skills and attitudes in the management of asthma exacerbations. The implementation method includes providing health education on asthma, clear signs of asthma attacks, asthma symptom control and risk factors for asthma patients, as well as self-management skills for asthma patients and efforts to monitor asthma signs and symptoms. Lung capacity is measured using a spirometry device connected to an Android mobile phone for direct measurement by health workers. The results of the community service show an increase in respondents' knowledge about asthma after a lecture intervention. This was tested using the Wilcoxon signed rank test, which showed a statistically significant increase in scores from pre-test to post-test. All changes were positive, indicating the effectiveness of the learning methods used. Spirometry measurements showed that the respondents' lungs were functioning well without significant airway obstruction, indicating that the intervention was successful in increasing knowledge about asthma and asthma control